Transfer Knowledge Teknologi Pertanian Modern berbasis Hidroponik Tipe Dutch Bucket pada Tanaman Cabai Merah (Capsicum annuum L.) di Desa Kepanjen, Kecamatan Gumukmas, Kabupaten Jember - Saputra, Tri Wahyu; Wijayanto, Yagus; Ristiyana, Suci; Purnamasari, Ika; Brian, Ida Bagus Daniswara; Burhanudin, Ahmad; Arthayasa, Raden Mochammad Yudishtira Ageng; Antonio, Ach. Farhad Septian (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
Red chili is one of the agricultural commodities cultivated in Kepanjen Village, Gumukmas District, Jember Regency. The unpredictable fluctuations in weather demand the application of modern agricultural technology that can enhance productivity while ensuring the sustainability of cultivation. As part of a community service program, the dutch bucket hydroponic system placed inside a greenhouse was introduced as an alternative solution for red chili cultivation. The program was implemented through three stages, namely preparation, implementation, and monitoring and evaluation, with students actively involved as facilitators and the community as the main partners. During the implementation stage, a greenhouse measuring 3 × 6 meters (18 m²) was successfully constructed, and a dutch bucket hydroponic installation was set up to accommodate 60 chili plants. The results of the activity showed that farmers and community members who participated in the socialization responded positively and demonstrated high enthusiasm toward the cultivation method applied. Thus, this program not only produced physical facilities in the form of a greenhouse and hydroponic installation but also contributed to improving the knowledge and skills of the community in adopting modern agricultural technologies.